Employment Quality in the Livestock Sector in Uruguay. A Case Study: A Case Study - Riella, Alberto; Ramírez, Jessica (Agrociencia Uruguay, 2012)
In this article we present a case study of employment quality in livestock rearing. This activity occupies more than seventy percent of Uruguay’s exploited surface area and has historically contributed a large proportion of the country’s exports. Despite its economic and social importance, since it employs sixty percent of permanent workers in rural production, there has been a remarkable lack of research on the working conditions or the characteristics of the jobs generated. The aim of this study is to gather information about working conditions and job characteristics so as to be able to estimate employment quality in the sector. Our sources are census data about livestock workers in the Tambores region, which straddles the border between the departments (provinces) of Tacuarembó and Paysandú. The methodology we use to measure employment quality is such that comparisons can be made with previous studies of these aspects in other production sectors in the country.